Perancangan UI/UX IngatCare Aplikasi Pengingat Minum Obat untuk Penderita Hipertensi - Faizi, Nur; Muhammad Imron Rosadi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to design UI/UX of IngatCare, a mobile-based medication reminder application for hypertensive patients using the Double Diamond methodology, which consists of four stages: Discover, Define, Develop, and Deliver. The design process began with interviews involving ten hypertensive patients to identify user needs, followed by the development of user personas, How Might We analysis, wireframe creation, and high-fidelity prototype design using Figma. The resulting prototype includes key features such as medication reminders, blood pressure recording, notification settings, and user guidance. Usability testing was carried out with ten respondents using the Single Ease Question (SEQ) and System Usability Scale (SUS). The SEQ results showed an average score of ≥6 across all scenarios, while the SUS obtained a score of 85, which falls into the Excellent category. The IngatCare prototype is proven to be user-friendly and aligned with the needs of hypertensive patients in managing their medication independently. Therefore, the IngatCare prototype is considered feasible to be further developed as a digital solution to improve medication adherence in hypertensive patients